Organic matter composition and thermal stability influence greenhouse gases production in subtropical peatland under different vegetation types - G.O. Akinbi; L.W. Ngatia; J.M. Grace, III; R. Fu; C. Tan; S.O. Olaborode; T. Abichou; R.W. Taylor (Heliyon, 2022)
Peatlands are a major carbon (C) sink globally. Organic matter quality influence greenhouse gases production. However, little is known about how organic matter from different vegetation types, influences C composition and resultant greenhouse gases production in subtropical peatland. Anoxic incubation experiments were conducted using two types of peats with different botanical origin to assess C composition, CO2 and CH4 production. First peat had cypress dominance and the second knotted spikerush and water lily (spike + lily). Solid-state CPMAS 13C NMR determined C chemical stability, MESTA determined C thermal stability, stable isotopes for C source and gas chromatograph for carbon dioxide (CO2) and methane (CH4). The results indicated dominance of autochthonous C as indicated by δ13C signatures. Low thermal stable C (LTSC) dominated in litter, FL (fermentation layer) and spike + lily sediment, high thermal stable C was dominant in cypress peat. O-alkyl C strongly correlated with LTSC whereas aromatic C correlated negatively with R400 (LTSC:total C ratio). Generally, O-alkyl decreased and alkyl increased along litter-FL-peat continuum. Spike + lily peat exhibited initial stage of decomposition. Indicated by increased alkyl C, aromatic C and aromatic:O-alkyl ratio with increasing peat depth. Also, exhibited 3 times more CH4 and CO2 production compared to cypress peat that dominantly exhibited second stage of decomposition. O-alkyl C exhibited positive relationship with CH4 (P = 0.012, r2 = 0.57) and CO2 (P = 0.047, r2 = 0.41) production whereas R400 related positively with CH4 (P = 0.05, r2 = 0.40). Organic matter thermal and chemical composition varied between the peat types and thermally and chemically labile C influenced CO2 and CH4 production.